Gender Difference and Errors in Writing Narrative Texts among Indonesian EFL College Students - Sugianto, Riris; Rahman, Lalu Isnaeni; Putera, Lalu Jaswadi (Linguistics and ELT Journal, 2023)
This study aims at identifying and analyzing linguistic and textual errors in writing narrative texts committed by male and female students of the fourth-semester English department students. The focus is on finding the significant differences between male and female students in terms of the frequencies of linguistic and textual errors in their narrative texts and the factors contributing to the errors. Data were collected through writing tests. Data were analyzed and interpreted by quantitative descriptive analysis and multivariate analysis using Two Ways ANOVA (F-Test) to investigate the significant differences linguistic and textual errors. Then the types of linguistic and textual errors in the two groups of male and female students were compared using descriptive analysis and statistical analysis. The results show that 57.93% of linguistic errors occurred in female’s narrative writing, with 42.07% occurred in male’s. Meanwhile, 46.29% of textual errors occurred in female’s narrative writing, with 53.71% found in the male’s. Statistically, there was no significantly different interaction between male and female students in terms of textual error frequency in writing narrative text, with p = 0.975 (p > 0.05) at the level of significance a = 5 %. And there was a significantly different interaction between male and female students in terms of linguistic error frequency in writing narrative texts, with p = 0.029 (p < 0.05) at the level of significance a = 5%. Several factors that affect female and male students’ errors in their narrative text are intralingual interference, language transfer, lack of knowledge about the narrative text, and gender difference.